Simulation analysis of work posture and muscle fatigue in breaking and connecting contact terminal - Ruijian PAN; Xin LU; Conghan LIU; Chu CHEN; Lei LIU; Min LI (环境与职业医学)
BackgroundWhen live working line operators engage in upper limb operations, working for a long time with raising arms and the exposure to adverse ergonomic factors tend to increase muscle load, cause fatigue accumulation, and increase the risk of work-related musculoskeletal disorders (WMSDs). ObjectiveTo analyze work posture and associated muscle fatigue during executing breaking/connecting contact terminal, and identify adverse ergonomic factors of the work process. MethodsThis study recruited 10 volunteers to perform breaking/connecting contact terminal simulation. At a distance of 4.5, 3.5, and 2.5 m from the body to the wire, each performed the task 5 times. Visual 3D was used to analyze the kinematic data from motion capture. The surface electromyography (sEMG) signals of the deltoid, biceps, triceps, and brachioradialis were recorded during the simulation and analyzed for muscle fatigue using root mean square (RMS), median frequency (MF), and jointed EMG amplitude and spectrum analysis (JASA). After completion of each task, Borg scale was used to query the volunteers of their subjective fatigue. A 2-min rest was required between each distance. ResultsThe kinematic data from motion capture showed that in the entire process of the task, the right upper limb was higher when lifting, with the right shoulder joint maintaining flexion and fluctuating periodically between abduction and adduction, external and internal rotation, the right elbow joint maintaining flexion and supination. The frequency of task cycle showed a significant effect on the Borg scale scores (P<0.001, partial \begin{document}$ {η }^{2} $\end{document}=0.464); the distance showed no significant effect on the Borg scale scores (P>0.05, partial \begin{document}$ {η }^{2} $\end{document}=0.002); their interaction effect was not significant (P>0.05, partial \begin{document}$ {η }^{2} $\end{document}=0.020). The results of the sEMG signals showed that at a distance of 4.5 m, the volunteers had the highest percentages of maximal voluntary electrical activation (MVE%) in the deltoid and right brachioradialis and the lowest MF values in the deltoid and left brachioradialis after completing 5 task cycles. The results of JASA showed that fatigue was observed in brachioradialis and deltoid after completing 5 task cycles at a distance of 4.5 m, the right deltoid and right brachioradialis at a distance of 3.5 m, in the brachioradialis, deltoid, and left bicep at a distance of 2.5 m. ConclusionThe subjective fatigue of workers who engaged in breaking/connecting contact terminal elevates with more repetitive operations. Based on the sEMG and motion capture analysis, it can be found that improper distance between the workers and the target work area can increase the burden from poor posture and improper use of work equipment, and lead to muscle fatigue; the deltoid and brachioradialis are the key muscles of fatigue in this type of operation; changing the angle of the elbow joint and the shoulder joint during the process of the operation can affect the deltoid and brachioradialis exertion and loading.